2016
DOI: 10.1007/s00408-016-9925-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreased TGF-β1 and VEGF Release in Cystic Fibrosis Platelets: Further Evidence for Platelet Defects in Cystic Fibrosis

Abstract: Purpose Cystic fibrosis (CF) patients suffer from chronic lung inflammation. This inflammation may activate platelets. There are limited data on the role of platelet-secreted cytokines in CF. Platelet cytokines with inflammatory effects include vascular endothelial growth factor (VEGF) and transforming growth factor-β1 (TGF-β1). As levels of these cytokines are tenfold greater in serum than plasma due to platelet release, serum levels may be one index of platelet content; but a more specific index is release d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This result argues that RvD1 may affect another mechanism aside from TGF-β production by macrophages, which may result in increased parasite replication. Notably, TGF-β can be produced by many other cell types2526 and thus it is possible that the positive correlation between RvD1 and TGF-β plasma levels observed in our patient population could result from an effect in cells other than macrophages. Future studies investigating the role of RvD1 on other cell types in the context of Leishmania infection are needed to better understand these discrepancies between the in vivo and in vitro systems.…”
Section: Discussionmentioning
confidence: 94%
“…This result argues that RvD1 may affect another mechanism aside from TGF-β production by macrophages, which may result in increased parasite replication. Notably, TGF-β can be produced by many other cell types2526 and thus it is possible that the positive correlation between RvD1 and TGF-β plasma levels observed in our patient population could result from an effect in cells other than macrophages. Future studies investigating the role of RvD1 on other cell types in the context of Leishmania infection are needed to better understand these discrepancies between the in vivo and in vitro systems.…”
Section: Discussionmentioning
confidence: 94%
“…Coagulation factors V, XI, and XIII, and the TGFβ activator protein TSP1 are also stored in the alpha granules (15,16). Therefore, measuring TGF-β levels in blood samples is complex due to much higher TGF-β levels in serum (coagulated blood) compared to that in plasma (anticoagulated blood) (17). Thus, comparison of serum TGF-β levels between populations or during illnesses may be confounded by platelet counts, intrinsic platelet aggregation properties, and/or use of antiplatelet agents (17,18).…”
Section: Tgf-β Is a Mediator Of Thrombosismentioning
confidence: 99%
“…Therefore, measuring TGF-β levels in blood samples is complex due to much higher TGF-β levels in serum (coagulated blood) compared to that in plasma (anticoagulated blood) (17). Thus, comparison of serum TGF-β levels between populations or during illnesses may be confounded by platelet counts, intrinsic platelet aggregation properties, and/or use of antiplatelet agents (17,18). Both latent forms of TGF-β are released from platelets with the LLC and SLC conformations comprising 65 and 35%, respectively (19,20).…”
Section: Tgf-β Is a Mediator Of Thrombosismentioning
confidence: 99%
“…The close association of EMT (Particularly type-3 EMT which leads to metastasis) with cancer led to the identification that CFTR is often down-regulated in metastatic cancer cells [ 88 , 101 ]. Maloney et al, (2016) showed higher levels of circulating TGF-β1 in CF patients [ 102 ]. TGF-β1 decreases CFTR expression through the p38 MAPK pathway and interestingly this was shown to occur prior the classical EMT E-Cadherin to N-Cadherin shift with low TGF-β1 concentrations [ 103 ].…”
Section: Cystic Fibrosismentioning
confidence: 99%